Interacting with Presence. HCI and the Sense of Presence in Computer-mediated Environments - Waterworth, John (De Gruyter, 2014)
The experience of using and interacting with the newest Virtual Reality and computing technologies is profoundly affected by the extent to which we feel ourselves to be really 'present' in computer-generated and -mediated augmented worlds. This feeling of 'Presence', of "being inside the mediated world", is key to understanding developments in applications such as interactive entertainment, gaming, psychotherapy, education, scientific visualisation, sports training and rehabilitation, and many more. This edited volume, featuring contributions from internationally renowned scholars, provides a comprehensive introduction to and overview of the topic of mediated presence - or 'tele-presence' - and of the emerging field of presence research. It is intended for researchers and graduate students in human-computer interaction, cognitive science, psychology, cyberpsychology and computer science, as well as for experienced professionals from the ICT industry. The editors are all well-known professional researchers in the field: Professor Giuseppe Riva from the Catholic University of Milan, Italy; Professor John Waterworth from Umeå University, Sweden; Dianne Murray, an HCI Consultant and editor of the journal "Interacting with Computers".